RETRACTED: Use of ultrasonic screening in aquaculture for the directed formation sturgeon and salmon fish mature stocks - Korentovich Marina; Litvinenko Alexander; Egorov Aial; Zenkovich Polina; Litvinenko Liudmila (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001